Provoking Situations? Why Reenact “Student-Robot” Interaction, in L.A. or Anywhere - Sormani, Philippe; Hostettler, Audrey (Social Interaction. Video-Based Studies of Human Sociality, 2023)
This paper presents a practice-based video analysis of student-robot interaction in situ. In so doing, the paper explicates the double interest of provoking situations, both as a praxeological topic and pedagogical resource. Designed and developed as a hybrid study of instructional work, the paper combines video analysis and the practical reenactment of two contrasting episodes of student-robot interaction. This combined approach pursues two related aims. First, the paper explicates (some of) the “tutorial problems” (Garfinkel, 2002, chapter 4) resulting from the practical reenactment, problems that recast and complement the video analysis. In particular, the focal theme of situated agency in student-robot interaction will be revisited as an intricate phenomenon and pedagogical issue. Second, the paper offers a reflexive intervention in ethnomethodology/conversation analysis (EM/CA), insofar as it prospects a (relatively) new avenue for EM/CA research, both from within and contributing to its productive tensions. That is, the paper articulates the video reenactment of situated interaction as a heuristic strategy, while leveraging the (arguably) phenomenological difference between EM and CA on education as a methodological resource. The paper concludes with how and why the provocative impetus of science and technology studies (Woolgar, 2004) can, and perhaps should, be leveraged for prospective EM/CA studies more broadly, be it on their historically alluring home turf, Los Angeles, or anywhere else.